285 Surgical morbidity during COVID-19 pandemic – a gynaecology oncology persective. (13th November 2020) - Moran, S; Corry, E; Schaler, L; Ward, C; O'Brien, D; McVey, R; Walsh, T; Boyd, W; Brennan, D
Abstract : Introduction: COVID-19 has had significant repercussions on the provision of oncological surgical services worldwide. Within any Gynaecological Oncology service, careful consideration needs to be given when weighing up peri-operative risks & potential inpatient exposure to COVID-19 versus the risk of delaying surgery. Often, for these patients, deferral of surgery may result in disease progression. Since March 2020, we identified 118 Gynaecological Oncology patients referred to the Ireland East Gynaecological Group between the Mater Misericordiae University Hospital (MMUH) & St. Vincent's University Hospital (SVUH) for whom major oncological surgery was deemed clinically urgent. To minimise peri-operative morbidity and the risk of onward hospital transmission of COVID-19, screening questionnaires were administered before hospital admission. These screened for epidemiological risk, symptoms, recent travel & contacts. If asymptomatic, testing for SARS-CoV-2 was not performed. Methods: We analysed the clinical data of the above 118 patients to determine their baseline characteristics/risk factors for COVID-19, suspected diagnoses, surgical procedures & 7-day morbidity. Results: This cohort consisted of ovarian (n=57), endometrial (n=41), cervical (n=6) and vulvo-vaginal (n=14) cancer patients. 44% of cases were laparoscopic and 18% were major cytoreductive surgeries. All patients screened were deemed asymptomatic & low risk- therefore proceeded to surgery. 49 (41.5%) patients had a defined risk factor for COVID-19. 7-day post-operative morbidity was 13% (N=16). 3 patients met symptomatic criteria for COVID-19 testing post-operatively, however none tested positive. Conclusion: Careful patient selection based on risk factors and symptoms allows units to continue to perform safe oncological surgery during a pandemic.